2019
DOI: 10.1038/s41567-019-0570-0
|View full text |Cite
|
Sign up to set email alerts
|

Disorder-induced multifractal superconductivity in monolayer niobium dichalcogenides

Abstract: The interplay between disorder and superconductivity is a subtle and fascinating phenomenon in quantum many body physics. The conventional superconductors are insensitive to dilute nonmagnetic impurities, known as the Anderson's theorem 1 .Destruction of superconductivity and even superconductor-insulator transitions 2-10 occur in the regime of strong disorder. Hence disorder-enhanced superconductivity is rare and has only been observed in some alloys or granular states 11-17 . Because of the entanglement of v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
108
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(116 citation statements)
references
References 60 publications
8
108
0
Order By: Relevance
“…Recent theory has revealed that nonreciprocal charge transport occurs in non-centrosymmetric superconductors when vortices driven by the external charge current move among the asymmetric pinning potentials in the vortex flow regime 15 . In 2D NbSe 2 , the asymmetric pinning potentials naturally appear as a consequence of disorder 15 such as defects [30][31][32] in 2D crystals with inversion symmetry breaking, as shown in Fig. 1c.…”
Section: Max1mentioning
confidence: 97%
“…Recent theory has revealed that nonreciprocal charge transport occurs in non-centrosymmetric superconductors when vortices driven by the external charge current move among the asymmetric pinning potentials in the vortex flow regime 15 . In 2D NbSe 2 , the asymmetric pinning potentials naturally appear as a consequence of disorder 15 such as defects [30][31][32] in 2D crystals with inversion symmetry breaking, as shown in Fig. 1c.…”
Section: Max1mentioning
confidence: 97%
“…d,e) Reproduced with permission. [ 94 ] Copyright 2019, The Authors, published by Springer Nature. f) Reproduced with permission.…”
Section: Bcs Superconductorsmentioning
confidence: 99%
“…Therefore, the enhancement by both dopants could be understood by the formation of multifractal electron wavefunction. [ 94 ] Due to the limited resolution, direct observation of the multifractality remains to be a big challenge.…”
Section: Bcs Superconductorsmentioning
confidence: 99%
“…However we do not think this latter case is relevant to the standard s-wave superconductor studied here. Also very recently, it was found that, while the effect of disorder on the dichalcogenide NbSe 2 in bulk form is explained in terms of CDW-superconductivity competition and synergy [41], in monolayer NbSe 2 a much larger T c dome was discovered as a function of disorder and this has been proposed to be due to the wave-function multifractality in a 2D monolayer system [73,74]. Thus, disorder as a tuning parameter is finding relevance not only for the study of bulk superconductors with density waves but also for 2D materials such as monolayer transition metal dichalcogenides.…”
Section: Discussionmentioning
confidence: 99%